2015
DOI: 10.1589/jpts.27.2061
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a community-centered muscle strengthening exercise program using an elastic band on the physical abilities and quality of life of the rural elderly

Abstract: [Purpose] The purpose of this study was to examine the effects of a muscle strengthening exercise program using an elastic band on changes in the physical abilities and quality of life of the rural elderly. [Subjects] The subjects of this study were 46 elderly people (8 males, 38 females) aged 65 or older, who lived in a rural area and managed their daily lives independently. [Methods] The study’s exercise program was conducted 16 times for 80 minutes each session over an eight-week period. This program consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
29
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 14 publications
4
29
0
7
Order By: Relevance
“…26 Resistance band exercises are helpful in healthy and frail older adults. 27,28 Such exercises have been found to enhance muscle strength and endurance; 29,30 improve balance, agility, and gait speed; 29,31,32 promote muscle hypertrophy; 33 and boost lower extremity function. 34 Furthermore, resistance band exercises have been reported to improve functional ability, 29 increase cardiovascular endurance, 29,31 increase flexibility and range of joint motion, 29,35 and enhance overall physical fitness of older adults.…”
mentioning
confidence: 99%
“…26 Resistance band exercises are helpful in healthy and frail older adults. 27,28 Such exercises have been found to enhance muscle strength and endurance; 29,30 improve balance, agility, and gait speed; 29,31,32 promote muscle hypertrophy; 33 and boost lower extremity function. 34 Furthermore, resistance band exercises have been reported to improve functional ability, 29 increase cardiovascular endurance, 29,31 increase flexibility and range of joint motion, 29,35 and enhance overall physical fitness of older adults.…”
mentioning
confidence: 99%
“…14 For older adults, low-impact and stabilization exercises were more appropriate and easily promoted. 15 Elastic band exercises were found to be of low impact and stable and could improve cardiorespiratory capacity, muscle endurance, flexibility, balance, and quality of life in older adults 12,16,17 ; thus, they can be one of the appropriate choices for older adults with dementia.…”
mentioning
confidence: 99%
“…Kim et al 16 ) reported balance training in a standing position as an exercise that is helpful for improving activities that mainly use the lower extremities, such as gait, and training in a sitting position as somewhat helpful for improving balance ability. A study by Park et al confirmed that a community-centered muscle strengthening program using the elastic bands was effective at changing the physical functions and quality of life of the rural elderly 17 ) . Viccaro et al 18 ) , during their one-year observation of 500 veterans, found that poor TUG times, in addition to increasing the risk of falls, predispose to health decline and ADL performance problems in formerly fit people.…”
Section: Discussionmentioning
confidence: 96%